Integration in Modern Islamic Boarding Schools; Kulliyatul Mu'allimin Al-Islamiyyah (KMI) Gontor Curriculum - Nurrohmah Nurrohmah; Moh. Roqib (Transformasi Manageria: Journal of Islamic Education Management, 2024)
Along with the flow of modernization, Islamic boarding schools have experienced development. Starting from the Salafiyah (traditional) Islamic boarding school, it developed until the Khalafiyah (modern) Islamic boarding school model was born. The Salafiyah Islamic boarding school model with its old traditions prioritizes the study of classical Islamic books, while the Khalafiyah (modern) Islamic boarding school model has characteristics that combine Islam, science and culture. Modern Islamic Boarding School Darussalam Gontor is one of the modern Islamic boarding schools in Indonesia which has the Kulliyatul Mu'allimin Al-Islamiyah (KMI) program with the identity of implementing its own curriculum and not following the curriculum that has been planned by the government. KMI with the dormitory system indicates that for 24 hours the students' activities within the Islamic boarding school are an educational process. This research is a literature study that uses a qualitative approach. The results of this research are an analysis of the integration contained in the Kulliyatul Mu'allimin Al-Islamiyah (KMI) Gontor curriculum. The educational process contained in the KMI curriculum is integrated by combining general knowledge and Islamic religious knowledge which is reflected in all activities at Pondok Modern Darussalam Gontor. The education and teaching system combines intra-curricular, extra-curricular and co-curricular in one unit, with the uniqueness of combining 100% general knowledge and 100% religious knowledge.